Implementation of Coaching Techniques to Enhance School Principals’ Managerial Competence Through the TIRTA Framework - Ai Aisyah; H Hidayat (Journal of Science and Education (JSE), 2025)
This study examines the implementation of coaching techniques based on the TIRTA Framework (Action, Reflection, Follow-Up, and Execution) as a strategic approach to enhancing the managerial competence of primary school principals. Using a qualitative case study approach, the research was conducted at SDN Talagasari and involved the principal, senior teachers, and school supervisors as key informants. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that coaching through the TIRTA Framework gradually facilitates a transformation in the principal’s mindset—from administrative leadership to reflective and collaborative leadership. The Action phase enables the identification of real, context-based problems within the school; Reflection promotes self-evaluation and awareness of one’s role; Follow-Up guides the formulation of strategic plans based on reflective insights; and Execution showcases the internalization of new leadership values into the school’s work culture. These findings affirm that reflective coaching is not merely a technical intervention, but a transformative learning process that can foster adaptive and sustainable leadership. The TIRTA-based coaching technique has the potential to serve as a professional development model for school principals, one that could be integrated into national education supervision policies in a more contextual and human-centered manner.